Where we want to live reclaiming infrastructure for a new generation of cities - Gravel, Ryan 1972- (St. Martin's Press, 2016)
"After decades of sprawl, many American city and suburban residents struggle with quality of life issues related to traffic and its accompanying pollution and time drain, divided neighborhoods, and a non-walkable life. Architect Ryan Gravel argues that this can change. Cities have the infrastructure and capability to create a healthier, more satisfying way of life by remodeling and augmenting different parts of cities to connect neighborhoods and communities. Gravel came up with a way to do just that in his hometown with the Atlanta Beltline project, a 22-mile looped path built on long-dormant intersecting rail lines. It connects 40 diverse Atlanta neighborhoods to city schools, shopping districts, and public parks, and has already seen a huge payoff in real estate development and local business revenue. Similar projects are in the works around the country, from the Los Angeles River Revitalization and the Buffalo Bayou in Houston to the Midtown Greenway in Minneapolis and the Underline in Miami. In Where We Want to Live, Gravel presents an exciting blueprint for revitalizing cities to make them places where we truly want to live"--